Health awareness improvement through hand washing with soap with elementary school students at Tongging village (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Health behavior problems in school-age children are related to personal hygiene and the environment. One of the health problems is the lack of awareness of washing hands with soap. The purpose of this study was to determine the knowledge of elementary students in the Tongging village, Mako district. This type of research is qualitative research that intends to understand the phenomena about what is experienced by research subjects such as behavior, perception, motivation, ways of description in the form of words and language, in a special natural context and by utilizing various natural methods. The sample of this research is students of SD Negeri 044845 Tongging village, Kecamatan Karo district. The results showed that the majority of respondents had an increase in health-conscious knowledge through proper and proper hand washing.